FONTES E DOSES DE FÓSFORO PARA O MARACUJAZEIRO-AMARELO - Vander Mendonça (Revista Caatinga, 2006)
The purpose of this work was to evaluate the effects of phosphor dosages and sources on productivity and fruit quality of yellow passion fruit. The experiment was carried out in orchards in Lavrasmunicipality, Minas Gerais, Brazil. The experimental outline used was a 2 X 5 factorial on a randomized complete block design, with four replicates. The treatments were composed by two phosphor sources (super triple phosphate and termophosphate) and five dosages (6, 30, 60, 90 and 120 g/plant). Productivity, fruit number per plant, juice yield, total soluble solids (TSS), total titratable acidity (TTA), ratio TSS/TTA and peel thickness were evaluated. There was no productivity increase or improvement of the fruit quality for the treatments, except for the increases of TTA and peel thickness when Yoorin termophosphate was used as fertilizer.